2000
DOI: 10.1177/009127000004001209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telmisartan on the Steady‐State Pharmacokinetics of Digoxin in Healthy Male Volunteers

Abstract: A multiple‐dose, open‐label, two‐period, crossover randomized study was conducted in 12 healthy male volunteers to investigate the effect of multiple‐dose telmisartan on the steady‐state pharmacokinetics of digoxin. On day 1 of a 7‐day medication period, subjects received a loading dose of digoxin 0.5 mg in the morning, followed by an evening dose of digoxin 0.25 mg, either alone or together with telmisartan 120 mg administered in the morning. On the subsequent 6 days, either digoxin 0.25 mg or digoxin 0.25 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…(2000) have reported that when a single high dose of Telmisartan (120 mg once daily) is used with Digoxin (0.5 mg once followed by 0.25 mg daily for a week), the AUC, Cmax and trough concentration (Cmin) of Digoxin were increased by 50%, 22%, and 13% respectively. But since the trough plasma levels of Digoxin were not remarkably increased, it was concluded that the drug interaction was of little clinical significance [ 53 ]. Kamiyama et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2000) have reported that when a single high dose of Telmisartan (120 mg once daily) is used with Digoxin (0.5 mg once followed by 0.25 mg daily for a week), the AUC, Cmax and trough concentration (Cmin) of Digoxin were increased by 50%, 22%, and 13% respectively. But since the trough plasma levels of Digoxin were not remarkably increased, it was concluded that the drug interaction was of little clinical significance [ 53 ]. Kamiyama et al.…”
Section: Discussionmentioning
confidence: 99%